Do canto se fez o encanto: o diverso o verso de Martinho da Vila - Rangel, Patricia Luisa Nogueira (2019)
This thesis, entitled "From the singing was made the charm: the diverse in the verse of Martinho da Vila", aims to analyze the lyrics of the musical compositions of the artist Martinho José Ferreira, known by Martinho da Vila. As a multifaceted – poet, composer, singer and writer, the sambist uses his ability with words to deal with social issues such as economic, educational, ethnic, cultural and political issues, among others, which afflict the poor in particular. Martinho da Vila, in his 80s, completed in 2018, is a popular poet, since his compositions give voices to the silenced and live socially and culturally marginalized. The samba player is endowed with property in his words on social issues that afflict the majority of the Brazilian population, for when he left Duas Barras, in the interior of the State of Rio de Janeiro, as a child, he moved with his family to the capital, then Federal District, and lived in the Serra dos Pretos Forros, he could feel in the skin what it is to be poor, as well as the anguish and sufferings of this class. The relationship of Martinho da Vila with his family and the GRES Unidos de Vila Isabel are references to the life and professional trajectory that favor the artist's creation process, since his compositions reflect his experiences and experiences. Through analysis of the lyrics of musical compositions of authorship of the samba, with or without partnership, to see the diverse, because identities are thought, the black is exalted and his culture valued, afflictions and anxieties of the poor are revealed to society. Therefore, it is a fact that Martinho da Vila is an intellectual who works for the poor. Finally, in this work, it is possible to verify that through singing, the artist presents the charm of the diverse.